A Federative Model of the Church in Orthodox Theology - Pavel Ermilov (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The author continues his study of the ways in which the political concept of federation is used to describe church organisation, this time taking as a basis the texts of Orthodox authors. These writers borrowed the idea of a federative structure of early Christian communities from Protestant historians of the 18th century and from subsequent works of Protestant scholars, for whom such notions became a component of the prevailing doctrine. In the writings of Russian theologians the concept of federation seems to have travelled the same path as in the West, having come into use against the background of a general fascination with political projections in theology and having lost its relevance under the influence of various criticisms. In Greek theology the picture turns out to be much more complex. In the course of the development of Greek historiography in the nineteenth century, federalism and democracy were declared to be the characteristic features of the model of organisation of the Eastern Christian Church, developed through the synthesis of the new religion and Hellenistic culture. In the twentieth century these ideas were revised. In modern Orthodox theology there is an agreement on the incorrectness of describing the Church using the concept of federation. Nevertheless, this image has come to be used as a polemical cliché in intra-Orthodox discussion, which is used to denote any form of rejection of the monocentric model of Church unity.